John Neff on investing - Neff, John (John B.) (John Wiley & Son, 1999)
Packed with solid advice and guidance for anyone who aspires to using Neff's unique brand of value investing, John Neff on Investing offers invaluable lessons on using price-earnings ratios as a yardstick, to zeroing in on undervalued stocks, interpreting earnings histories and anticipating new market climates. A narrative of Neff's early days-My Road to Windsor-reveals the extraordinary mindset and humble circumstances that shaped his winning investment philosophy. By reproducing excerpts from his personal investment diaries, this book offers a unique opportunity to watch Neff in action over the years. A faithful, quarter-in-quarter-out chronicle of a life on Wall Street, the diaries provide unprecedented insights into the thinking behind some of his best (and worst) investment decisions, while tracing the evolution of his innovative investment style.